CarHero – “Mobile Application for Automobile Users and Mechanics” - Nurul Shahida, Sabirin (Universiti Malaysia Sarawak (UNIMAS), 2020)
A mobile application is a type of application software designed to run a mobile device such as a smartphone or tablet computer. The usage of mobile apps makes people having easy lifestyle and living. The use of mobile apps can be seen in areas such as communication, social media, shopping business, banking, education and more. Nowadays, many people face problem in getting help when their car suddenly breaks down on the road. Sometimes, it takes too long for the mechanic to diagnose and repair the car where, the automobile user needs a long time for their car to be repaired. This project aims to develop a mobile application for customers and mechanics in Kampung Belawai, Sarawak called CarHero. The development of the proposed system is to improve the previously existing system. Overall, this thesis introduces the background of the system, methodology used, design of the system, interface of the system and achievements of the system.